algebra

posted by .

what is the simpliest form of the equation
3 sqrt 750 + 3 sqrt 2058 - 3 sqrt 48
possible answers
14 3sqrt6
17.5 3sqrt6
33 3sqrt6
10 3sqrt6

  • algebra -

    ∛750 = ∛√125√6 = 5∛6
    √2058 = ∛343∛6 = 7∛6
    √48 = √8√6 = 2∛6

    so we have (5+7+2)∛6 = 14∛6

    use cbrt(n) or cuberoot(n) for ∛n
    sqrt means square root.

  • algebra -

    Thank you so much for the help

  • algebra -

    the answer was 10 3sqrt6

  • algebra -

    oops. I added 2 instead of subtracting. Clever of them to include that wrong choice!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  2. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  3. Mathematics

    sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.
  4. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  5. Algebra

    Multiplying sq rts sqrt18a^7b times sqrt27a^8b^6 Jake 1214- 18 = 9 * 2 then sqrt 18 = 3sqrt2 sqrt a^7 = a^3 * sqrt a 27 = 9 * 3 then sqrt 27 = 3 sqrt3 sqrt a^8 = a^4 sqrt b^6 = b^3 Now just multiply the like-terms together. 3sqrt6 …
  6. Math (URGENT)

    Use calculator - answer correct to 3 places. a. 3sqrt17 + 2sqrt15 / 5sqrt7 = 10.644 b. 2sqrt11 - 3sqrt2 + 15sqrt10 + 5sqrt5 = 61.005 c. 4.3sqrt6.9 / 1.7sqrt57 = 50.163 Can someone check my answers?
  7. Algebra

    I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) d.y = sqrt(-x-1) …
  8. algebra

    how can you write the expression with rationalized denominator?
  9. linear algebra check

    Use the Gram-Schmidt process to transform the basis [1 1 1] , [0 1 1] , [2 4 3] for the Euclidean space R3 into an orthonormal basis for R3. (Enter each vector in the form [x1, x2, ...]. Enter your answers as a comma-separated list.) …
  10. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions